Culture and nature in conserving the indigenous water system in rural China: A case study of the ancient village of Hongcun. Issue 2 (3rd May 2020) - Li, Chuo; Chen, Hong
Abstract: Rapid economic development and population growth combined with urbanization and changes of industrial and agricultural practices have considerably modified indigenous water systems in rural China. By focusing on the historical evolvements and challenges in using and conserving the traditional water system in the village of Hongcun in Anhui Province, China, this study reveals the multiple ecological, social and cultural frames that have shaped the development of the indigenous waterscape. It emphasizes that a holistic approach to landscape conservation with integrated natural and cultural constructs can facilitate a meaningful change towards sustainable land use and resilient water management in the rural village. Continued investments in tourism and urban infrastructure should be challenged by a comprehensive development model that places a higher priority on sustainable goals that would support the village and help it to endure and flourish in the future.